Kinetics of response to first‐ and second‐line therapies in multiple myeloma: Assessment by both M‐spikes and light chains. (19th November 2021) - Lebel, Eyal; Li, Xuan; Paul, Harminder; Masih‐Khan, Esther; Bhella, Sita; Chen, Christine; Prica, Anca; Reece, Donna; Tiedemann, Rodger; Trudel, Suzanne; Kukreti, Vishal
Abstract: Objectives: The prognostic value of kinetics of response to multiple myeloma (MM) therapy is controversial. We aimed to expand the knowledge on this topic by reviewing the kinetics of response to both first‐ and second‐line MM therapy, utilizing a homogeneously treated cohort and analyzing separately both M‐spike and light chain (LC) responses for each patient. Methods: We reviewed all patients who received first‐line cyclophosphamide, bortezomib and dexamethasone induction followed by autologous transplant with melphalan and lenalidomide maintenance in our center between 2007 and 2019. Results: Analyzing 360 patients, we observed no correlation between response kinetics to first‐ versus second‐line therapy at the individual patient level. Time to best response to first‐line therapy was not a predictor of outcome; however, longer time to best response was highly predictive of a favorable outcome in the second‐line setting, independent of other factors. Patients with IgA‐MM cleared their M‐spike faster than IgG‐MM, probably reflecting different half‐lives of these isotypes rather than disease biology, as the clearance of LC in both subtypes was similar. Conclusions: Analyzing both M‐spike and LC responses in a homogenously treated cohort, we identified important insights regarding the prognostic value of kinetic patterns. Prospective analysis may shed more light on unsolved questions.